Dynamic resonance: unpacking Ghanaian traditional knowledge through proverbs for modern socio-environmental innovation - Quarshie, Benjamin; Poku, Kelcy Menkah (Frontiers in Human Dynamics, 2025)
Traditional knowledge reflects the essence of a community, embodying its truths and ancestral lineage. Preserving this knowledge is vital for maintaining identity and cultural roots. However, viewing it as the sole marker of ethnic ancestry overlooks other factors, such as genetics and the interplay of beliefs and practises. Beliefs and practises, shaped by cumulative wisdom, represent a dynamic core of traditional knowledge influenced by geography, experiences, cultural encounters, and resource availability. Tradition is not static but evolves with time, adapting to the needs of the era. Thus, it is essential to critically evaluate traditional knowledge within its temporal context to distinguish sustainable practises from those that may hinder progress. This paper examines select traditional knowledge embedded in proverbs from two Ghanaian ethnic cultures, Akan and Ewe, through the lens of 21st-century sustainable practises. The focus is to demonstrate that whilst some traditional knowledge endures, others align with modern skills like creativity, innovation, critical thinking, and collaboration—key to socio-environmental sustainability. The paper begins by appreciating Ghanaian traditional knowledge and its practical applications in daily life. It then presents a selection of proverbs with their interpretations, followed by a critical review guided by 21st-century benchmarks with the aid of ChatGPT 4.0 and Gemini 1.5 pro language modelling Artificial Intelligence (AIs) after authentication of the selected proverbs by language experts who are also vested in Ghanaian proverbs. The analysis highlights the nuanced fabric of traditional knowledge, identifying some proverbs that remain relevant and adaptable for daily usage in educational and industrial organisations to elicit 21st-century competencies. The paper concludes with recommendations for scholarly contributions and educational initiatives grounded in traditional knowledge. These initiatives aim to foster sustainable, innovative practises that meet contemporary needs, bridging cultural heritage and modernity.